2012
DOI: 10.1111/j.1365-2141.2012.09123.x
|View full text |Cite
|
Sign up to set email alerts
|

A rare fraction of drug‐resistant follicular lymphoma cancer stem cells interacts with follicular dendritic cells to maintain tumourigenic potential

Abstract: SUMMARY Follicular lymphoma (FL) comprises nearly 25% of non-Hodgkin lymphoma cases and is clinically characterized by initial sensitivity to chemotherapy followed by relapse. FL stroma contains a special type of stromal cell found in germinal centre of lymph nodes—the follicular dendritic cell (FDC). We first isolated tumourigenic cells from the FL cell line FLK-1 by side population (SP) technique, and found that SP cells, which express ABCG2, were enriched by chemotherapy and radiation treatments. In vitro, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 42 publications
1
39
0
Order By: Relevance
“…For example, breast and pancreatic cancer cells expressing CD44 increase metastatic ability [87]. However, this does not simply mean that only the CD44 + /CD24 −/low BCSCs are able to metastasize, several BCSC phenotypes are found to co-exist in a tumor and each phenotype shows its own unique metastatic potential and sensitivity to therapeutic regimens [88].…”
Section: Potential Biomarkers For Bcscsmentioning
confidence: 99%
“…For example, breast and pancreatic cancer cells expressing CD44 increase metastatic ability [87]. However, this does not simply mean that only the CD44 + /CD24 −/low BCSCs are able to metastasize, several BCSC phenotypes are found to co-exist in a tumor and each phenotype shows its own unique metastatic potential and sensitivity to therapeutic regimens [88].…”
Section: Potential Biomarkers For Bcscsmentioning
confidence: 99%
“…Among the genes modulated, CXCL12 (mean fold change 24 h (FDC-HK vs. C) ¼ 31.9) stands out as a prominent factor in chemotactic responses. Both lymphoma cells and stromal cells, including FDCs, secrete CXCL12 (34,35). Moreover, drug-resistant cancer hours, and then were subjected to adhesion assays on plates precoated with BSA 1% (nonspecific adhesion), VCAM1, or fibronectin.…”
Section: Bkm120 Hampers Cxcl12/cxcr4-mediated Migration and Signalingmentioning
confidence: 99%
“…stem FL cells interact with FDCs in a CXCL12/CXCR4-dependent manner to resist chemotherapy (34). In addition, PI3K inhibitors targeting p110a or p110g isoforms interfere with CXCL12-induced migration of CLL cells (36).…”
Section: Bkm120 Hampers Cxcl12/cxcr4-mediated Migration and Signalingmentioning
confidence: 99%
“…High degrees of intrafollicular CD68+ and programmed cell death ligand 1+ macrophage infiltration are associated with a shorter time to transformation in FL [14]. Furthermore, cancer stem cells or the tumor-initiating cells of BCL maintain their tumorigenic potential via interplay with the TME [15, 16]. Previous studies have demonstrated that the protective effect of the TME was mediated through tumor-stroma cell interactions, especially direct cell-to-cell contact between tumor cells and stromal cells [17-19].…”
Section: Introductionmentioning
confidence: 99%